2003
DOI: 10.1007/s00268-003-6893-z
|View full text |Cite
|
Sign up to set email alerts
|

18‐Fluorodeoxyglucose‐Positron Emission Tomography in Inflammatory Breast Cancer

Abstract: Inflammatory breast cancer (IBC) is the most aggressive form of locally advanced breast cancer. It can be diagnosed based on a clinical or pathologic basis. We evaluated the usefulness of (18)F-fluorodeoxyglucose-positron emission tomography (FDG-PET) scans for diagnosing and staging IBC. We retrospectively reviewed the medical records of seven consecutive patients with IBC who underwent FDG-PET scanning for the initial staging. Four patients had follow-up PET scans after chemotherapy. All seven patients prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 13 publications
4
15
0
Order By: Relevance
“…9 In another small retrospective series of IBC, distant metastases were revealed by FDG-PET in 4 of 7 cases. 18 So, our series confirms the high percentage of IBC presenting with distant lesions at diagnosis. FDG-PET imaging for initial staging of standard breast cancer has shown debatable results for locoregional disease, but has proved its value for detecting distant metastases in locally advanced breast carcinoma patients.…”
Section: Discussionsupporting
confidence: 83%
“…9 In another small retrospective series of IBC, distant metastases were revealed by FDG-PET in 4 of 7 cases. 18 So, our series confirms the high percentage of IBC presenting with distant lesions at diagnosis. FDG-PET imaging for initial staging of standard breast cancer has shown debatable results for locoregional disease, but has proved its value for detecting distant metastases in locally advanced breast carcinoma patients.…”
Section: Discussionsupporting
confidence: 83%
“…PET/CT showed hypermetabolic uptake in the affected breast in all but 1 patient in this study. These findings are similar to the results of Baslaim et al and van der Hoeven et al (24,25) but differ from those results regarding the value of 18 F-FDG PET in early breast cancer (stages 1 and 2), for which PET has shown a lower accuracy (18,26,27), likely secondary to the low tumor volume. Diffuse hypermetabolic skin thickening was noted in all patients and is a unique feature of IBC that is infrequent in all other subgroups of breast cancer.…”
Section: Discussionsupporting
confidence: 78%
“…A single PET study of seven patients with IBC demonstrated diffusely increased or intense foci of increased uptake in enlarged breasts with increased skin uptake [17].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, findings of IBC on magnetic resonance imaging (MRI) and functional positron emission tomography/computed tomography (PET/CT) are scarce in the published literature [14][15][16][17]. In this retrospective study, we report the imaging findings using MRI, PET/CT, mammography, and sonography at the time of initial presentation in IBC patients.…”
Section: Introductionmentioning
confidence: 95%